2017
DOI: 10.3390/en10050624
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Dynamic Economic Dispatch with Demand Side Management of Residential Loads and Electric Vehicles

Abstract: Abstract:In this paper, a multi-objective optimization method based on the normal boundary intersection is proposed to solve the dynamic economic dispatch with demand side management of individual residential loads and electric vehicles. The proposed approach specifically addresses consumer comfort through acceptable appliance deferral times and electric vehicle charging requirements. The multi-objectives of minimizing generation costs, emissions, and energy loss in the system are balanced in a Pareto front ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The proposed energy management approach minimizes the electricity cost, equation (1), while satisfies problem's restrictions through multiple equality and inequality constraints. The system loads divide into deferable and nondeferable loads in which deferable loads can be shifted within their ADT limits [17], [18]. Four types of appliances with different ADT including dishwashers, clothes washers, clothes dryers, and heating and ventilation systems are considered as deferable loads.…”
Section: Problem Formulationmentioning
confidence: 99%
“…The proposed energy management approach minimizes the electricity cost, equation (1), while satisfies problem's restrictions through multiple equality and inequality constraints. The system loads divide into deferable and nondeferable loads in which deferable loads can be shifted within their ADT limits [17], [18]. Four types of appliances with different ADT including dishwashers, clothes washers, clothes dryers, and heating and ventilation systems are considered as deferable loads.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Demand-side management (DSM) is the best approach for supply-demand matching by which customer demand can be shaped to improve utilization factors and load balance [22]. In addition, DSM programs may defer capital investment in generation, transmission and distribution networks and storage, and improve system load [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of changing the electricity demand profile through Demand Side Management (DSM) programs was also considered. A multi-objective optimization method for solving dynamic economic dispatch with the DSM of individual residential loads and electric vehicles was proposed in [8]. The result of the six-generator test system showed that shifting deferrable loads can significantly flatten the load profile and reduce peaks.…”
Section: Introductionmentioning
confidence: 99%